Effects of dietary formic acid polymer supplementation on growth performance, blood parameters, and intestinal health in lipopolysaccharide-challenged broilers - Zhou, Guohui; Ge, Yilin; Fu, Yuemeng; An, Changfei; Li, Changjin; Li, Yang; Yang, Weiren; Jiao, Ning; Chen, Jiali (Frontiers in Microbiology, 2025)
This experiment was performed to investigate the impacts of formic acid polymer (FAP) supplementation to the diet on the growth performance, blood metabolites, as well as intestinal barrier function related indicators of broilers under lipopolysaccharide (LPS) stimulation. A total of 450 1-day-old male Arbor Acres broilers with similar body weights were assigned to one of three experimental groups: control (CON) group, basal diet; LPS group, basal diet with LPS (1 mg/kg body weight) challenge; LPS+FAP group, basal diet supplemented with FAP (1,000 mg/kg) and LPS (1 mg/kg body weight) challenge. Each group had 6 replicates of 25 broilers. LPS was injected on days 17, 19, and 21. Samples were collected on day 21, 3 h post-challenge. The experiment lasted 21 days. LPS treatment reduced growth performance, immune function, and caused systemic inflammation, intestinal barrier damage, and microbiota dysbiosis in broilers. However, FAP supplementation significantly reversed these effects by reducing the feed-to-gain ratio and serum levels of interleukin (IL)-1β and tumor necrosis factor-α (P < 0.05), while increasing serum levels of complement C4, IL-10, and immunoglobulin M (P < 0.05). FAP also improved villus height, trefoil factor family, and mucin 2 levels, decreased caspase activities (P < 0.05), and reduced harmful bacteria while promoting beneficial bacteria. To sum up, supplementing 1,000 mg/kg of FAP to the diet effectively enhanced immune function, and mitigated the systemic inflammatory response and intestinal barrier damage caused by LPS, thereby improving broiler growth performance.